An antique building wood component and a microcapsule modified anti-corrosion and anti-aging preparation method thereof
Patent Information
- Application Number
- CN202611183172.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-09
AI Technical Summary
这些方法虽有一定效果,但存在明显缺陷:1)药剂以物理吸附或简单沉积为主,易因雨水冲刷、紫外线分解而流失,保护周期短(通常仅3-8年),需频繁维护;2)高毒性药剂对施工人员及环境不友好;3)处理后的木材表面常有药剂析出或颜色改变,影响古建筑“修旧如旧”的修复美学要求
1.长效智能防护:微胶囊的壁层提供了智能释放屏障。当环境湿度升高(触发囊壁溶胀)、木材受真菌侵蚀产生有机酸(触发pH响应)或温度变化时,囊壁通透性可调控变化,实现活性成分的按需、精准释放,克服了传统药剂前期突释、后期失效的缺点,保护周期预计可达20-30年。
Smart Images

Figure CN122876493A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ancient building protection and wood material modification technology, specifically to a long-term protection method for repairing and replacing wooden components of antique buildings and the products made therefrom, particularly a method for modifying wooden components of antique buildings based on reactive microcapsule in-situ bonding technology and its products. Background Technology
[0002] Antique-style wooden components (such as beams, columns, purlins, rafters, etc.) are important carriers for inheriting historical culture. Their materials are mainly natural woods such as pine, fir, and oak. These components are exposed to complex outdoor environments for a long time and are mainly threatened by three aspects of deterioration: (1) biological decay: wood decay fungi, insects and other biological attacks lead to decay and insect infestation; (2) photo-oxidative aging: solar ultraviolet rays cause lignin degradation, surface powdering, discoloration and strength reduction; (3) moisture attack: rainwater and moisture cause dry and wet cycles, which lead to cracking and deformation of components and aggravate biological corrosion.
[0003] Currently, the protection of wooden components mainly relies on traditional chemical treatments, such as copper chromium arsenide (CCA) and quaternary ammonium copper (ACQ), applied through spraying, brushing, or pressure impregnation. While these methods have some effectiveness, they have significant drawbacks: 1) The agents primarily rely on physical adsorption or simple deposition, making them easily washed away by rainwater and decomposed by ultraviolet light, resulting in a short protection period (usually only 3-8 years) and requiring frequent maintenance; 2) Highly toxic agents are unfriendly to construction workers and the environment; 3) After treatment, the wood surface often shows agent leaching or discoloration, affecting the aesthetic requirement of "restoring the old as it was" in the restoration of ancient buildings.
[0004] In recent years, microencapsulation technology has attracted attention in the materials field due to its controllable release characteristics. Existing technologies include attempts to microencapsulate insect repellents, antibacterial agents, or phase change materials for application in wood. However, these technologies often suffer from the following problems: First, the functions are limited, focusing on insect prevention or temperature regulation, and failing to systematically solve the complex problems faced by antique-style wooden components; Secondly, the adhesion between microcapsules and wood matrix is mostly physical or simple pore filling, with weak bonding force. Under outdoor temperature and humidity changes, freeze-thaw cycles and other stresses, they are prone to falling off and failing. Finally, the release of microcapsules is mostly passive diffusion, which cannot respond to environmental changes to achieve intelligent and on-demand release, resulting in early burst release of the drug or insufficient protection in the later stages.
[0005] Therefore, developing a microcapsule modification technology that can form a stable bond with the wood matrix, has multiple protective functions, and can intelligently respond to environmental stimuli is of urgent need and great significance for achieving long-term, environmentally friendly, and authentic protection of wooden components in antique buildings. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention aims to provide a method for preparing antique-style wooden architectural components and their microcapsule-modified anti-corrosion and anti-aging properties. This invention designs a composite functional microcapsule with reactive wall material and utilizes a specific process to chemically fix it in situ within the wood, thereby endowing the wooden components with long-lasting, intelligent, and multi-layered protective properties while preserving the original appearance and texture of the wood to the greatest extent possible.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing microcapsule-modified anti-corrosion and anti-aging materials for antique-style wooden architectural components, characterized by comprising the following steps: S1. Preparation of composite microcapsule emulsion: A core material solution containing preservative components, anti-aging components and hydrophobic components is emulsified and dispersed in an aqueous phase containing reactive wall material monomers, and a microcapsule emulsion with a core-shell structure is formed by polymerization reaction, wherein the wall material has active groups that can react with the hydroxyl groups of wood; S2. Microcapsule loading: The wooden component is impregnated in the microcapsule emulsion, and the microcapsules are penetrated into the wood using a vacuum-pressurization process; S3. In-situ curing and fixation: The impregnated wood components are heat-treated to allow the active groups of the microcapsule wall material to chemically bond with the wood cell wall components, thereby fixing the microcapsules inside the wood.
[0008] Further, in step S1, the anti-corrosion component includes, but is not limited to, one or more of low-toxicity organic bactericides such as copper azole (e.g., CA-C, CA-B), propiconazole, and tebuconazole. The anti-aging component includes a compound system of ultraviolet absorbers (e.g., benzotriazoles, benzophenones) and hindered amine light stabilizers (HALS). The hydrophobic component includes organosilicon resin prepolymers, long-chain alkylsiloxanes, or paraffin wax. The core material solvent is preferably a low-boiling-point organic solvent such as ethanol or ethyl acetate.
[0009] Furthermore, the reactive wall material is a polymeric material rich in active groups such as hydroxyl, amino, and silanoxy groups on its molecular chain. Preferably, it is chitosan and its derivatives (such as carboxymethyl chitosan, quaternized chitosan) or natural polymers such as gelatin and gum arabic modified with silane coupling agents (such as KH-550, KH-560). These active groups can undergo dehydration condensation or silanol condensation reactions with the hydroxyl groups on the cellulose and hemicellulose of the wood cell wall during subsequent heat treatment.
[0010] Further, in step S1, the polymerization reaction is an interfacial polymerization or in-situ polymerization initiated by adjusting the pH or adding a crosslinking agent. A preferred embodiment is as follows: carboxymethyl chitosan is dissolved in water to form an aqueous phase, and the core material solution is dispersed in the aqueous phase at a high shear rate of 8000-12000 rpm to form a stable O / W type fine emulsion. Subsequently, the pH of the emulsion is adjusted to 4.5-5.5 with an acid (such as acetic acid), and a crosslinking agent such as glutaraldehyde is slowly added. The reaction is carried out in a water bath at 50-70°C for 2-4 hours, allowing the wall material to crosslink and solidify at the oil-water interface, forming microcapsules with a particle size mainly distributed in the range of 1-10 micrometers. This particle size range ensures that the microcapsules can effectively enter most of the cell cavities (typically 10-200 micrometers in diameter) and pits of wood, while avoiding excessive penetration due to their small size, which would result in insufficient surface concentration.
[0011] Furthermore, before step S2, a pretreatment step is included: the wooden components (preferably pine, fir, oak, or other commonly used ancient building woods) are dried to a moisture content of less than 15%, and can be selectively subjected to light microwave treatment (power 300-500W, time 1-3 minutes) or short-term vacuum treatment to loosen the wood structure, open the pore channels, and enhance the subsequent impregnation effect.
[0012] Further, the vacuum-pressurization process described in step S2 is as follows: first, maintain a vacuum of -0.08 MPa to -0.1 MPa for 30-60 minutes to completely extract the air from the wood cell cavities and pores; then, maintain a pressure of 0.5 MPa to 1.2 MPa for 1-3 hours to force the microcapsule emulsion deep into the wood.
[0013] Further, step S3 specifically includes: S31. Preliminary drying: The impregnated wood components are slowly dried at a low temperature of 50-60℃ until the moisture content is 20-40%, allowing the moisture to evaporate and the microcapsules to initially deposit and accumulate in the pores of the wood; S32. Heat curing: The preliminarily dried wood components are heat-treated at 80-120℃ for 2-6 hours. This step is crucial, as the heat causes the active groups (-OH, -NH2, -Si(OR)3) of the wall material to react chemically with the hydroxyl groups of the wood cell wall, forming strong covalent bonds (such as ether bonds COC, Si-OC bonds), realizing the fundamental transformation of the microcapsules from "physical filling" to "chemical anchoring". At the same time, the hydrophobic components in the core material may also partially cross-link, forming a hydrophobic network inside the wood.
[0014] Furthermore, the preferred conditions for the thermosetting are treatment at 105±5℃ for 3-5 hours.
[0015] Secondly, the present invention provides an antique-style wooden architectural component prepared by any of the above methods. The interior of the wooden component contains composite microcapsules fixed by chemical bonding, wherein ether bonds and / or Si-OC bonds are formed between the wall material of the microcapsules and the cell wall of the wood.
[0016] Furthermore, the wooden components are structural members such as beams, columns, purlins, and rafters made of pine, fir, or oak. After treatment by the method of this invention, its corrosion resistance level reaches the highest level (mass loss rate ≤5%) of GB / T 13942.1-2009 "Durability of Wood Part 1: Laboratory Test Methods for Natural Corrosion Resistance"; after 72 hours of boiling water extraction, its effective component retention rate is greater than 90%; after 1000 hours of QUV accelerated aging test (ASTM G154 cycle), its surface color difference ΔE and bending strength retention rate are more than 5 times higher than those of untreated wood.
[0017] Compared with the prior art, the present invention has the following significant advantages: 1. Long-lasting intelligent protection: The wall layer of the microcapsule provides an intelligent release barrier. When the ambient humidity increases (triggering capsule wall swelling), wood is eroded by fungi and produces organic acids (triggering pH response), or the temperature changes, the permeability of the capsule wall can be regulated and changed, realizing the on-demand and precise release of active ingredients. This overcomes the shortcomings of traditional drugs that have a sudden release in the early stage and failure in the later stage. The protection period is expected to reach 20-30 years.
[0018] 2. Stable bonding and strong resistance to loss: The chemical bonds (ether bonds, Si-OC bonds) formed by in-situ thermosetting strongly anchor the microcapsules to the wood cell wall, solving the problem of agent loss caused by rain erosion, shrinkage and swelling of outdoor wooden components. It is environmentally friendly and greatly improves the duration of effectiveness.
[0019] 3. Multifunctional integrated design: A single treatment simultaneously imparts efficient anti-corrosion, insect-proof, UV-resistant, hydrophobic, and dimensional stability properties to the wood, simplifying the cumbersome procedures of multiple treatments in the restoration of ancient buildings and improving restoration efficiency and quality.
[0020] 4. Perfectly in line with the principle of "restoring the old as it was": the process does not change the macroscopic color, texture and feel of the wood, all functional components are sealed inside, and the surface of the components can be normally treated with traditional ground application, oiling and painting techniques, which fully meets the requirements of authenticity and aesthetics in the restoration of cultural relics.
[0021] 5. Green and environmentally friendly, safe construction: Microencapsulation technology reduces the direct contact between operators and chemical agents during construction, and the wall materials (such as chitosan) and low-toxicity agents used are environmentally friendly, which is in line with the concept of modern cultural relic protection and sustainable development. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a flowchart of the preparation process of the present invention. Detailed Implementation
[0024] Embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings. Preferably, the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0025] In the description of this invention, it should be understood that the terms "length," "width," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicating orientation or positional relationships, are based on the orientation or positional relationships shown in the accompanying drawings and are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention. Furthermore, in the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.
[0027] Example 1
[0028] 1. Core material preparation: Weigh 2.0 parts by weight of environmentally friendly copper azole (CA-C), 1.0 parts by weight of benzotriazole ultraviolet absorber (UV-326), 0.5 parts by weight of light stabilizer (HALS-770), and 1.0 parts by weight of octyltriethoxysilane, and dissolve them together in 10 parts by weight of anhydrous ethanol. Stir well to obtain a clear core material solution.
[0029] 2. Aqueous phase preparation: Dissolve 3.0 parts by weight of carboxymethyl chitosan (degree of substitution 0.8, viscosity 200 mPa·s) in 97 parts by weight of deionized water, add 1.0 part by weight of compound emulsifier (Span-80 and Tween-80 mass ratio 3:2), and stir magnetically until completely dissolved.
[0030] 3. Emulsification and Polymerization: In a high-speed shear emulsifier, the core material solution was slowly added dropwise to the aqueous phase, and emulsification was maintained at 10,000 rpm for 20 minutes to form a uniform and stable O / W emulsion. The pH of the emulsion was adjusted to 5.0 with 1% acetic acid solution. Under slow stirring, 1.5 parts by weight of 25% glutaraldehyde aqueous solution was added dropwise, and the reaction was carried out in a constant temperature water bath at 60℃ for 3 hours. After the reaction was completed, the mixture was cooled to room temperature to obtain a milky white carboxymethyl chitosan-based microcapsule emulsion with a particle size distribution of 1-8 micrometers.
[0031] 4. Wood pretreatment: Take a 20mm×20mm×100mm heartwood specimen of Pinus sylvestris var. mongolica and dry it to a moisture content of 12%. Place the specimen in an impregnation tank.
[0032] 5. Vacuum-Pressure Impregnation: Close the impregnation tank and evacuate to -0.095 MPa, maintaining this pressure for 45 minutes. While maintaining the vacuum, inject the above microcapsule emulsion into the tank to completely immerse the specimen. Then, introduce compressed nitrogen gas and pressurize to 0.8 MPa, maintaining this pressure for 2 hours. After depressurization, remove the specimen and absorb any surface liquid with filter paper.
[0033] 6. Preliminary drying and heat curing: Place the impregnated specimens in a 55℃ forced-air drying oven and dry until the moisture content is about 30%. Then transfer them to a 105℃ oven for heat treatment for 4 hours.
[0034] 7. Curing: After heat treatment, the specimen is placed under standard conditions of 20°C and 65% relative humidity for one week to obtain the modified wood component described in this invention (marked as sample M).
[0035] Comparative Example 1 Using the same core material solution as in Example 1 (without microencapsulation), the same specification of Pinus sylvestris specimens were directly impregnated. The process parameters were the same as steps 4-6 in Example 1, resulting in a sample treated only with physical impregnation agent (labeled as sample C1).
[0036] Comparative Example 2 The same microcapsule emulsion as in Example 1 was used, but the curing step after impregnation was only low-temperature drying at 60°C, without heat treatment at 105°C, to obtain the sample (marked as sample C2).
[0037] Performance testing and characterization 1. Chemical Bonding Characterization (FTIR): Fourier Transform Infrared Spectroscopy was used to analyze samples M, C2, and the untreated material. Results showed that sample M exhibited bonding at 1050 cm⁻¹. -1 Near (Si-OC stretching vibration) and 1250 cm -1A distinct new absorption peak appears near the COC asymmetric stretching vibration, while there is no peak or the peak is extremely weak in sample C2 and untreated material, proving that Si-OC and ether bonds are formed between the microcapsule wall material and the wood in sample M.
[0038] 2. Corrosion Resistance Test: Referring to GB / T 13942.1-2009, a 12-week laboratory decay test was conducted on the samples using brown rot fungus (Gloeophyllum trabeum) and white rot fungus (Trametes versicolor). Results: The mass loss rate of untreated wood reached 45.2% (brown rot) and 38.7% (white rot); the loss rate of sample C1 was 8.5% and 7.1%; the loss rate of sample C2 was 5.2% and 4.3%; the mass loss rate of sample M was only 2.1% and 1.8%, reaching the highest level of corrosion resistance (strong corrosion resistance).
[0039] 3. Anti-leaking test: Following AWPA E11-16 standard, the samples were boiled in boiling water for 72 hours, dried, and the retention rate of the main active ingredient (copper) was determined. Results: The copper retention rate of sample M was 92.5%, while that of sample C1 was only 35.8%, and that of sample C2 was 68.4%. This demonstrates that chemical bonding significantly improves anti-leaking properties.
[0040] 4. UV Aging Resistance Test: Following ASTM G154, a QUV accelerated aging test was conducted using a UVA-340 lamp (cycle: 8 hours of UV irradiation at 60℃, followed by 4 hours of condensation at 50℃). After 1000 hours of testing, the surface color difference ΔE and flexural strength loss rate were evaluated. Results: The untreated material had a ΔE of 25.4 and a strength loss rate of 41%; sample M had a ΔE of only 4.8 and a strength loss rate of 7.5%. The anti-aging performance of sample M (based on color difference and strength retention) was more than 5 times better than that of the untreated material.
[0041] 5. Dimensional stability: The radial dimensional changes of the samples were measured under conditions of 20℃, 30%RH, and 90%RH, and the shrinkage resistance (ASE) was calculated. The ASE of sample M reached 65%, which is a highly significant improvement compared to the untreated material (ASE about 10%).
[0042] 6. Surface morphology and texture: Observed with the naked eye and stereomicroscope, the surface color and texture of sample M are basically no different from the untreated raw wood. There is no chemical exudation, no greasy feeling, and the touch is still the natural texture of wood.
[0043] Example 2
[0044] The difference between this embodiment and Example 1 is that the wall material uses 3.0 parts by weight of gelatin, and 1.0 parts by weight of silane coupling agent KH-550 is added when preparing the aqueous phase. Grafting modification is performed by pre-reaction at 60°C for 1 hour. Subsequent emulsification, impregnation, and curing processes are the same as in Example 1. The performance of the obtained sample is comparable to that of Example 1. FTIR shows a clear Si-OC characteristic peak, confirming that the silane-modified gelatin wall material also achieves chemical bonding with wood.
[0045] Example 3
[0046] The difference between this embodiment and Embodiment 1 is that the treated material is square timber of Chinese fir (Cunninghamia lanceolata), commonly used in ancient buildings, with dimensions of 50mm × 50mm × 1000mm. The thermosetting conditions were adjusted to 110℃ for 3.5 hours. The improved performance trend of the treated Chinese fir component is consistent with that of the pine specimen, meeting the requirements for load-bearing components in ancient buildings.
[0047] The above embodiments are merely preferred embodiments of the present invention, and the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions, and improvements made by those skilled in the art to the specific types of wall materials and core materials, and process parameters, without departing from the principles and spirit of the present invention, should be included within the scope of protection of the present invention. The scope of protection claimed by the present invention is determined by the claims.
Claims
1. A method for preparing antique-style wooden architectural components and their microcapsule-modified anti-corrosion and anti-aging properties, characterized in that, Includes the following steps: S1. Preparation of composite microcapsule emulsion: A core material solution containing preservative components, anti-aging components and hydrophobic components is emulsified and dispersed in an aqueous phase containing reactive wall material monomers, and a microcapsule emulsion with a core-shell structure is formed by polymerization reaction, wherein the wall material has active groups that can react with the hydroxyl groups of wood; S2. Microcapsule loading: The wooden component is impregnated in the microcapsule emulsion, and the microcapsules are penetrated into the wood using a vacuum-pressurization process; S3. In-situ curing and fixation: The impregnated wood components are heat-treated to allow the active groups of the microcapsule wall material to chemically bond with the wood cell wall components, thereby fixing the microcapsules inside the wood.
2. The preparation method according to claim 1, characterized in that, In step S1, the anti-corrosion component includes copper azole and / or propiconazole; the anti-aging component includes ultraviolet absorber and hindered amine light stabilizer; and the hydrophobic component includes silicone resin prepolymer or long-chain alkanes.
3. The preparation method according to claim 1 or 2, characterized in that, In step S1, the reactive wall material is a chitosan derivative or gelatin modified with a silane coupling agent; the polymerization reaction is interfacial polymerization or in-situ polymerization initiated by adjusting the pH or adding a crosslinking agent.
4. The preparation method according to claim 3, characterized in that, Step S1 specifically includes: dissolving carboxymethyl chitosan in water to form an aqueous phase, shearing and emulsifying the core material solution into the aqueous phase at a rotation speed of 10000±2000 rpm to form an O / W type emulsion, adjusting the pH of the system to 4.5-5.5, adding glutaraldehyde crosslinking agent, and reacting at 50-70℃ for 2-4 hours to form the microcapsule emulsion, wherein the particle size of the microcapsules is mainly distributed in the range of 1-10 micrometers.
5. The preparation method according to claim 1, characterized in that, Prior to step S2, a pretreatment step is included: drying the wood component to a moisture content of less than 15%, and optionally subjecting it to microwave treatment or vacuum pretreatment to enhance its permeability.
6. The preparation method according to claim 1, characterized in that, The vacuum-pressurization process described in step S2 is as follows: first, maintain a vacuum of -0.08 MPa to -0.1 MPa for 30-60 minutes, and then maintain a pressure of 0.5 MPa to 1.2 MPa for 1-3 hours.
7. The preparation method according to claim 1, characterized in that, Step S3 specifically includes: S31. Preliminary drying: Dry the impregnated wooden components at 50-60℃ until the moisture content is 20-40%; S32. Heat curing: The pre-dried wooden components are heat-treated at 80-120℃ for 2-6 hours to promote the chemical bonding of the active groups of the wall material with the wood.
8. The preparation method according to claim 7, characterized in that, The thermosetting conditions are 105±5℃ for 3-5 hours.
9. An antique-style wooden architectural component prepared by the method described in any one of claims 1-8, characterized in that, The interior of the wooden component contains composite microcapsules fixed by chemical bonding, and the wall material of the microcapsules forms ether bonds and / or Si-OC bonds with the wood cell walls.
10. The antique-style wooden architectural component according to claim 9, characterized in that, The wooden components are beams, columns, purlins, and rafters made of pine, fir, or oak, with a corrosion resistance grade reaching the highest level of GB / T 13942.1-2009. After boiling in water, the effective component retention rate is greater than 90%, and the UV aging resistance is more than 5 times higher than that of untreated materials.